Exploration of the Influence of External Factors on Purchase Intention: The Role of Store Image and Brand Awareness at Sociolla Store Pakuwon Mall Surabaya - Priskilla E.E. Napitupulu; Hananiel M. Gunawan; Yanuar Dananjaya (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The rapid growth of the cosmetics and beauty industry in Indonesia has attracted significant attention to the increasing consumer interest. This study, conducted at Sociolla Store in Pakuwon Mall Surabaya, aims to examine the impact of Price Level, Merchandise, Sales Promotion Girl, and Architecture Project on Purchase Intention through Store Image, Perceived Value, and Brand Awareness. A causal research design using a quantitative approach was employed, with data analyzed using SPSS. A questionnaire was distributed to 100 respondents residing in Surabaya who had visited the store at least twice within the last three months. The results of this study indicate that Price Level has a positive but not significant effect on Store Image, whereas Merchandise, Sales Promotion Girl, and Architecture Project have a positive and significant effect on Store Image. Furthermore, Store Image positively and significantly influences Perceived Value and Brand Awareness, while Perceived Value and Brand Awareness have a positive and significant effect on Purchase Intention.